"Self-cleaving" 2A peptide from porcine teschovirus-1 mediates cleavage of dual fluorescent proteins in transgenic Eimeria tenella. (December 2016) - Tang, Xinming; Liu, Xianyong; Tao, Geru; Qin, Mei; Yin, Guangwen; Suo, Jingxia; Suo, Xun
Abstract The "self-cleaving" 2A sequence of picornavirus, which mediates ribosome-skipping events, enables the generation of two or more separate peptide products from one mRNA containing one or more "self-cleaving" 2A sequences. In this study, we introduced a single 2A sequence of porcine teschovirus-1 (P2A) linked to two fluorescent protein genes, the enhanced yellow fluorescent protein (EYFP) gene and the red fluorescent protein (RFP) gene, in a single cassette into transgenicEimeria tenella (EtER). As expected, we obtained two separated protein molecules rather than a fused protein, although the two molecules were translated from the same mRNA carrying a single "self-cleaving" 2A sequence. Importantly, RFP led by a secretion signal was secreted into parasitophorous vacuoles, while EYFP localized mainly to the nucleus of EtER. Our results demonstrate that the "self-cleaving" 2A sequence actively mediated cleavage of polyproteins in the apicomplexan parasiteE. tenella.